Summary proceedings [of the] annual meeting of the Board of Governors. - International Bank for Reconstruction and Development (Washington, D.C. The Bank, 1946)
Annual.
Title varies: 1946-49, Annual meeting of the board of governors; proceedings (varies slightly)
Keywords: International Monetary Fund -- Congresses; Foreign exchange -- Congresses